"Suction Tube Uterine Tamponade" for treatment of refractory postpartum hemorrhage: Internal feasibility and acceptability pilot of a randomized clinical trial. Issue 1 (26th October 2021) - Cebekhulu, Sylvia N.; Abdul, Hazmath; Batting, Joanne; Chauke, Lawrence; Dlakavu, Fuziwe; Fawcus, Sue; Govender, Logie; Majeke, Busiwe; Mbongozi, Xolani; Singata‐Madliki, Mandisa; Middleton, Katrin; Mlandu, Philiswa; et al.
Abstract: Objective: To assess feasibility and acceptability of a novel, low‐cost "Suction Tube Uterine Tamponade" (STUT) treatment for refractory postpartum hemorrhage (PPH). Methods: We allocated patients with refractory PPH by randomly ordered envelopes to STUT or routine uterine balloon tamponade (UBT, Ellavi free‐flow system) in 10 hospitals in South Africa. In the STUT group, a 24FG Levin stomach tube was inserted into the uterine cavity and vacuum created with a vacuum pump or manual vacuum aspiration syringe. Results: For this internal pilot study, 12 participants were allocated to STUT and 12 to UBT. Insertion failed in one of each group and was recorded as difficult in 3/10 STUT and 4/9 UBT insertions respectively (five missing data). There were two laparotomies and one intensive care unit admission in the UBT group. Pain during STUT insertion was graded as none/mild in 9/10 and severe in 1/10. The experience of the STUT procedure was graded as fine in 4/11 and "uncomfortable but acceptable" in 7/11. Conclusion: STUT is feasible and acceptable, justifying continuation of our trial. These data will also inform a large World Health Organization trial to test effectiveness of uterine tamponade methods. The numbers are too small to support any clinical recommendation. Abstract : A novel, low‐cost "Suction Tube Uterine Tamponade" procedure was found to be feasible and acceptable, justifying continuation of an ongoing randomized trial of effectiveness.